Restless Knowledge, Capabilities and the Nature of the Mega-Firm - Bloch, Harry; Metcalfe, S. (Springer, 2015)
An evolutionary approach to economics recognises that the economy is an open system subject to change from within. One important evolutionary feature is the emergence of dominant firms in many important sectors of the global economy. We argue that these firms have distinguishing characteristics that contribute to their evolutionary fitness and have powerful impact on the process of innovation. We designate these firms as mega-firms. We locate the distinctive competitive advantage of the mega-firm in its ability to cope with restless knowledge. The mega-firm imagines and then pursues its products, technology and resources. It does not take its environment as given. It develops extensive capabilities from the specialised knowledge of large numbers of individuals, thereby reaping economies through the coordination of a division of labour. Importantly, firm capabilities expand organically from the interaction of the knowledge of individuals, enhanced by introspection and creative problem solving, which provides potential protection for the firm against the ravages of creative destruction in the competitive process. Most importantly, the mega-firmorganises itself to enhance innovation without destroying cohesion, which means that its structure and functions are both historically specific and changing over time. Thus, the mega-firm is a restless firm.